Improvement to Increase the Effectiveness Coverage in Roda Lensa - Kusumo, Prasetyo Wisnu; Nizar, Adirizal (The Indonesian Journal of Business Administration, 2015)
Abstract - Media development in Indonesia is already advanced. Print types slowly began to move into the digital world and electronics. Growing number of media companies are seeing rapid progress in the world of mass media. Unfortunately the current media development in Indonesia is insignificant compared to the education of its people. The development of the print media in Indonesia is experiencing strong turbulence. A new generation of readers began to emerge, namely the generation of readers who do not read things more seriously, the generation who do not like the hassle of language in print, and a generation that does not like to face in print. Sustainability of life of heavy media with their ability to capture the reader wishes. Through the presentation of news content related to the needs of readers, they will turn the industry believed the media, particularly the print type in Indonesia.Roda Lensa is an online media that stands in November 2013. Roda Lensa, which has target audience at the age of 15-35 years, adolescents and young adults, carrying the motto "POSITIVE and FRESH" where Roda Lensa always try to give the latest news as well as to motivate its readers. Roda Lensa realize now is the time when all things goes mobile. In addition to factors that are not a lot of capital involve, online media is a type of media that are easy to make, as well as easily accessed by readers. This research is expected to make Roda Lensa becomes more effective as well as to improve the news content and also makes it more attractive in the eyes of the readers. And for that, by evaluating the condition of the company through open interviews, deficiencies can be identified and recommendations for improvement can be given. The recommendations given in this study is expected to improve the effectiveness, improve the content and increasing the interest of the reader, both new readers and old readers. Keywords: online media, Operational, Operational Management